A web-based reflective architecture for process support environment - Yamaguti, Marcelo Hideki (2002)
In this paper we present the WRAPPER: a Web-based Reflective Architecture for Process suPport EnviRonment. The base level of the reflective architecture is compound by objects representing the various components involved in a process specification, as well as, the elements of the software development environment. The meta-level is compound of meta-objects that are activated by message flows between the base level objects during the process enactment. The meta-objects can collect data about the process, and they can even change the behavior of the base level objects and consequently change the own process. Additionally, to achieve an integrated environment, the architecture provides facilities to aggregate remote CASE tools from different platforms. The WRAPPER uses the Web as its platform and it provides mechanisms to define and to control distributed objects (and meta-objects) over the Web, based on a CORBA middleware. As benefits, the architecture provides: flexibility for controlling and adapting the process, distribution of the environment in the Web; and heterogeneity for aggregating different components to the environment. We present the structure of the reflective architecture, as well as, the implemented prototype of the process support environment.